2021
DOI: 10.21037/gs-21-83
|View full text |Cite
|
Sign up to set email alerts
|

Mucin-type sialyl-Tn antigen is associated with PD-L1 expression and predicts poor clinical prognosis in breast cancer

Abstract: Background: A recent study showed that mucin-type sialylated O-linked glycans could induce the increased expression of PD-L1 via binding to Siglec receptors. However, the relationship between the expression of the mucin-type sialyl-Tn antigen (sTn) and PD-L1 remains unclear in breast cancer (BC).Therefore, we investigate the clinicopathological and prognostic effects of sTn expression and its relationship with PD-L1 expression in BC tissues. Methods: We retrospectively analyzed the clinical data of 380 invasiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Normally, Siglec-15 is weakly expressed in macrophage. However, M-CSF (Macrophage Colony-Stimulating Factor) induces the appearance of Siglec-15 in tumor-associated macrophages in response to tumor or inflammatory factor stimulation, remodeling the tumor microenvironment and promoting tumor metastasis and poor prognosis [ 33 , 34 ]. Macrophages are an important component of TME immune cells that promote tumorigenesis, progression, metastasis and have acquired a lot of interest as potential therapeutic targets [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Normally, Siglec-15 is weakly expressed in macrophage. However, M-CSF (Macrophage Colony-Stimulating Factor) induces the appearance of Siglec-15 in tumor-associated macrophages in response to tumor or inflammatory factor stimulation, remodeling the tumor microenvironment and promoting tumor metastasis and poor prognosis [ 33 , 34 ]. Macrophages are an important component of TME immune cells that promote tumorigenesis, progression, metastasis and have acquired a lot of interest as potential therapeutic targets [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study has shown that hypersialylated cancer cells increase siglec-7 and sigle-9 signaling, driving macrophage differentiation to an immunosuppressive phenotype, further supporting the notion that glycoconjugates can modulate immune checkpoints [ 34 ]. Additionally, a retrospective study on breast cancer patients showed that patients exhibiting a high STn/PD-L1 profile had poorer prognoses and might benefit from therapeutic strategies focusing on both fronts [ 35 ].…”
Section: Unusual O -Linked Glycan Structures and T...mentioning
confidence: 99%
“…Breast cancer Tn (57-92%), STn (33-42%), T (32%) [87,[108][109][110] Gastric cancer STn (50-78%), Tn (92%), T (20%) [111,112] Colorectal cancer Tn (51-98%), STn (75-87%), T (20%) [87,113,114] Lung cancer Tn (16%), STn (33%), T (10%) [87] Pancreatic cancer Tn (53%), STn (56-97%), T (16-48%) [87,115] Skin cancer Tn (33-50%), STn (24%), T (25%) [87,116] Brain cancer Tn (51%), STn (80%), T (20%) [87] Mesenchymal cancers No expression [87]…”
Section: Human Cancer Type % Of Truncated Glycans Expressed By Cancer...mentioning
confidence: 99%